2013
DOI: 10.2460/javma.242.2.242
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of pH and refractometry index with calcium concentrations in preparturient mammary gland secretions of mares

Abstract: Results suggested that the pH test with the standard value set at a pH of 6.4 would be useful in the management of preparturient mares by predicting when mares are not ready to foal. This was accomplished with equal effectiveness of measuring calcium carbonate concentration with a water hardness kit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 11 publications
1
18
2
1
Order By: Relevance
“…Korosue and others (2013) measured the pH twice daily in 28 mares, and these authors reported that a pH of 6.4 determined by a semiquantitative method presented a positive predictive value for foaling within 72 hours of 97.9 per cent and negative positive predictive value within 24 hours of 99.4 per cent. As most mares foal during the late evening or early morning (Bain and Howey 1975), we considered that determining pH only once daily during early evening would facilitate prefoaling management.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Korosue and others (2013) measured the pH twice daily in 28 mares, and these authors reported that a pH of 6.4 determined by a semiquantitative method presented a positive predictive value for foaling within 72 hours of 97.9 per cent and negative positive predictive value within 24 hours of 99.4 per cent. As most mares foal during the late evening or early morning (Bain and Howey 1975), we considered that determining pH only once daily during early evening would facilitate prefoaling management.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we hypothesise that measuring of pH in the mammary gland secretions once a day early in the evening would enable us to predict foaling. Additionally, Korosue and others (2013) found associations between pH and CaCO 3 determined by a semiquantitative method. However, the correlations between pH of mammary gland secretion and its correspondent electrolytes (ie, (Ca 2+ ), (Na + ), (K + ) (Mg 2+ ) and (Cl − )) have not been reported.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…In addition to monitoring electrolytes, it has been reported that a reduction in pH occurred in peri‐parturient mares, and that twice daily determination of pH could effectively predict parturition (Korosue et al . ). This is valuable information, as a single pH measurement undertaken each evening is simple, practical and cost effective.…”
Section: Monitoringmentioning
confidence: 97%
“…Recently, Korosue and others (2013) demonstrated that a pH strip test of mammary gland secretions can be useful in the management of preparturient mares by predicting when mares are not ready to foal (negative predictive value for foaling within 24 hours of 99.4 per cent, which is similar to calcium carbonate concentration testing). Negative predictive value was also accomplished with equal effectiveness in measuring calcium carbonate concentration with a water hardness kit.…”
mentioning
confidence: 99%